Trade, Luxury Goods and a Growth Enhancing Tariff - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2016)
This article presents a Ricardian model of trade with learning-by-doing to study the effect of barriers to trade in products with low growth potential on the long-run economic growth. The model shows that, when elasticity of demand for the product with a lower learning potential is greater than unity, a tariff imposed on this product can shift the demand toward the product with a higher learning potential, thus enhancing growth in the exporter economy. Therefore, although with some possible negative effect on the welfare in the short run, barriers for the export of natural luxury goods may be beneficial for developing economies in the long run, since they increase their incentive to develop sectors with higher growth potential.
Keywords: F11; F15; F41; O41; 330; trade barriers; luxury goods; learning-by-doing